2019
DOI: 10.1371/journal.pone.0220984
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 and DNAJA2 limit CFTR levels through degradation

Abstract: Cystic Fibrosis is caused by mutations in the CFTR anion channel, many of which cause its misfolding and degradation. CFTR folding depends on the Hsc70 and Hsp70 chaperones and their co-chaperone DNAJA1, but Hsc70/Hsp70 is also involved in CFTR degradation. Here, we address how these opposing functions are balanced. DNAJA2 and DNAJA1 were both important for CFTR folding, however overexpressing DNAJA2 but not DNAJA1 enhanced CFTR degradation at the endoplasmic reticulum by Hsc70/Hsp70 and the E3 ubiquitin ligas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 74 publications
1
31
0
Order By: Relevance
“…These misfolded ER clients, which are not suitable for ERAD must be cleared from the ER through the lysosome alternative by autophagic or non-autophagic pathways. It has been shown that Hsp70 chaperones have a dual function in protein degradation, as they can select misfolded proteins for either the general protein degradation pathways, the proteasome system, or the lysosome degradation machinery [ 33 , 34 , 45 , 46 , 47 , 48 , 57 , 58 ]. Our present data demonstrate that immature NKCC2 is recognized by STCH, a component of the Hsp70 system, and degraded by two different pathways that function in a complementary way to regulate NKCC2 turnover.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These misfolded ER clients, which are not suitable for ERAD must be cleared from the ER through the lysosome alternative by autophagic or non-autophagic pathways. It has been shown that Hsp70 chaperones have a dual function in protein degradation, as they can select misfolded proteins for either the general protein degradation pathways, the proteasome system, or the lysosome degradation machinery [ 33 , 34 , 45 , 46 , 47 , 48 , 57 , 58 ]. Our present data demonstrate that immature NKCC2 is recognized by STCH, a component of the Hsp70 system, and degraded by two different pathways that function in a complementary way to regulate NKCC2 turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Among the members of 70 kDa heat shock proteins, Hsc70 (heat shock cognate protein, Hsp73/HSPA8) and Hsp70 (Hsp72/HSPA1A) have been extensively studied and have distinct biological functions despite their high sequence homology [ 33 , 34 , 53 ]. Consequently, the roles of Hsp70 and Hsc70 in the ERAD of several transmembrane proteins such CFTR, NCC, ENaC, and HERG have been thoroughly investigated [ 24 , 45 , 46 , 47 , 48 , 57 ]. Under cellular stress conditions, it is assumed in general that Hsc70 associates with newly synthesized misfolded proteins to induce their ER associated degradation by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, DNAJB6 and DNAJA1 were recently shown to have opposing effects on the levels of cellular polyglutamine aggregates, meaning their cellular abundances alone modulate aggregate formation [162]. Moreover, the levels of co-chaperones DNAJA1 and DNAJA2 regulate CHIP/HSP70-mediated degradation of mutant CFTR: while both co-chaperones are needed for CFTR folding, increased levels of DNAJA2 promote degradation of CFTR [163]. Other studies show how inhibition of JDPs can regulate chaperone activities directly-a mechanism that can be used to treat chaperone-related diseases.…”
Section: Regulation Of Chaperone Activitymentioning
confidence: 99%
“…This activity of DJA2 is comparable to re-folding of the model substrate luciferase, such that DJA1 is unable to substitute 45,46 . Recent findings suggest that DJA2 also promotes CHIP-mediated ERAD of CFTR 47 . How these conflicting outcomes are determined remains largely unknown.…”
mentioning
confidence: 99%